Theoretical Analysis of a Three-Phase Bidirectional Isolated DC-DC Converter Using Phase-Shifted Modulation - Zhong Yih Tan; Nadia Mei Lin Tan; Ida Suzana Hussain (Institute of Advanced Engineering and Science, 2018)
A three-phase bidirectional isolated dc-dc converter consists of two six-pulse two-level active converters that enable bidirectional power flow by introducing a lag phase-shift angle of one converter with respect to the other converter. This paper explains the operating modes of a three-phase bidirectional isolated dc-dc converter in detail, taking into account the transfer of energy between the dc voltage sources and high-frequency ac inductances in the three-phase bidirectional isolated dc-dc converter. The power flow of the dc-dc converter is also examined based on the operating modes.